Assessment of air pollutants when burning alternative fuels - Olena Levytska; Artem Sikorsky (Challenges and Issues of Modern Science)
Purpose. The aim of the work is to identify potential agricultural waste that can become energy sources, which will significantly reduce the cost of the operation of small and medium-sized boilers and provide cost savings for small and medium-sized businesses. Design / Method / Approach. An analytical review of scientific articles, information from Internet resources is carried out in order to determine the most common and suitable for the purposes of energy production using agricultural waste, as well as the experience of enterprises in the production of alternative fuels is analyzed. Findings. The analysis of information sources has shown that wood waste, straw, flax fescue, sunflower husks can be attributed to secondary raw materials that can be used as an energy resource. Technologies for obtaining briquettes and pellets are applicable to such waste and can be used for the operation of low- and medium-sized boiler units. The calculations carried out by the researchers show that emissions from the incineration of the industrial gases such as processed coke-oven and blast-furnace gases and also solid waste are comparable and for a number of chemicals are less than during the combustion of popular fuel oils. Theoretical Implications. Assessment of pollutant emissions from the combustion of different types of fuels will show the level of environmental impact and stimulate the scientific search for the most optimal and environmentally friendly fuels. Practical Implications. The studies conducted by the authors stimulate the choice of alternative energy sources, which is an economically profitable and environmentally sound action. Originality / Value. The comparative characteristics of alternative and traditional fuels are relevant due to the exhaustibility of traditional fuels. In addition, the use of waste as an energy resource leads to the abolition or reduction of costs associated with waste management and eliminates the cost of money for the extraction of energy resources. Research Limitations / Future Research. In the future, it is planned to expand the range of alternative energy sources and analyze emissions from their combustion. Of course, an important stage of the research will be the comparison of emissions from the combustion of the studied fuels and traditionally used in the energy industry fuels. Paper Type. Practitioner Paper.